Attenuation of Skeletal Muscle Atrophy Induced by Dexamethasone in Rats by Teaghrelin Supplementation - Jhuo, Cian-Fen; Hsieh, Sheng-Kuo; Chen, Wen-Ying; Tzen, Jason T. C. (Molecules (Basel, Switzerland), 2023)
Muscle atrophy caused by an imbalance between the synthesis and the degradation of proteins is a syndrome commonly found in the elders. Teaghrelin, a natural compound from oolong tea, has been shown to promote cell differentiation and to inhibit dexamethasone-induced muscle atrophy in C2C12 cells. In this study, the therapeutic effects of teaghrelin on muscle atrophy were evaluated in Sprague Dawley rats treated with dexamethasone. The masses of the soleus, gastrocnemius and extensor digitorum longus muscles were reduced in dexamethasone-treated rats, and the reduction of these muscle masses was significantly attenuated when the rats were supplemented with teaghrelin. Accordingly, the level of serum creatine kinase, a marker enzyme of muscle proteolysis, was elevated in dexamethasone-treated rats, and the elevation was substantially reduced by teaghrelin supplementation. A decrease in Akt phosphorylation causing the activation of the ubiquitin–proteasome system and autophagy for protein degradation was detected in the gastrocnemius muscles of the dexamethasone-treated rats, and this signaling pathway for protein degradation was significantly inhibited by teaghrelin supplementation. Protein synthesis via the mTOR/p70S6K pathway was slowed down in the gastrocnemius muscles of the dexamethasone-treated rats and was significantly rescued after teaghrelin supplementation. Teaghrelin seemed to prevent muscle atrophy by reducing protein degradation and enhancing protein synthesis via Akt phosphorylation.